DENTAL PATIENTS WITH PSYCHOLOGICAL PROBLEMS - Talha M Siddiqui; Aisha Wali; Muhammad Ain ul Haq; Sadia Naqvi; Nasratullah Zhwand; Wahid Ibrahimi; Sajad Ahmad Hakimi (Pakistan Oral & Dental Journal, 2021)
The study was aimed to assess the role of dental surgeons in identifying dental patients with psychological problems. A cross-sectional study was conducted and a convenience sampling technique was used. The study was conducted from August 2018 to February 2019 and was approved by the ethical review board, (Ethical Approval no. BDC/ERB/2018/001). A pre-structured validated questionnaire was used for the survey. Two hundred seventy two registered GDPs and Postgraduates from different teaching hospitals present on the day of data collection were included in the study. These questionnaires were then distributed by the researchers to the dental surgeons of each designated hospital and filled up questionnaires were collected on the same day. The participants included were 208 GDPs and 64 postgraduates. The present study reported that 179(74.9%) GDP and 60(25.1%) PG encountered dental patients with psychological problems. One hundred thirty (74.3%) GDPs and 45(25.7%) PGs provided simple treatment and manage the psychological illness. Based on these findings of the study, it is concluded that dental surgeons do come across problems in identifying their dental patients with psychological problems.